Motivation and study habits of working adults : a case study of Masters students in Open University Malaysia - Loo, Sze Wei; Tuan Fatma Tuan Sulaiman,; Wardah Mohamad,; Zorah Abu Kasim, (2011)
The objective of this study was to explore what motivates working adults to continue with their studies and what are their study habits. A group of OUM masters students from the Faculty of Business and Management were studied using the case study approach. The main implication from the case findings is that working adults are highly motivated in pursuing their studies and that there are many sources of motivation for them. A new job, increased career prospects, gaining knowledge, a pay increase and filling their time are some of the factors that motivate these students to further their studies. Their study habits also differ widely from a short time span to full concentration, from early in the morning to late at night and from formal sessions to minutes of stolen time. The research looked at how the students studied and how motivated they are. The findings from the study are useful to students, academicians and university administrators alike. Students can seek to learn from their friends’ experiences, academicians can tailor the learning process to cater to students’ needs and behaviour, whilst university administrators can find ways to market their programmes and retain their students. As the research has initiated some new questions in the behaviour of working adults, it can serve as the basis for further research in the area. (Abstract by authors)